Getting ahead of the game: Experiential learning for groundwater governance in Ethiopia - ElDidi, Hagar; Zhang, Wei; Gelaw, Fekadu; Petris, Caterina de; Blackmore, Ivy; Teka, Natnael; Yimam, Seid; Mekonnen, Dawit Kelemework; Ringler, Claudia; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2023)
The goal of this study is to assess the potential of game-based experiential learning in raising awareness and stimulating discussions about groundwater resource systems, the social dilemma in groundwater management, and the need for institutional arrangements (rules) governing this shared resource, as well as whether such awareness and community discussions lead to actual change in groundwater governance in Ethiopia. Groundwater management is highly complex, with many users sharing the same resource often without realizing their interconnectedness. Behavioral experiments (games) that simulate real-life common-pool resource use have shown promise as an experiential learning tool for improving resource governance. This study pilots an experiential learning intervention in Ethiopia using a groundwater gameto help raise awareness of groundwater over-extraction and improve understanding of the importance of collective action in governance. The Meki River catchment in rural Ethiopia is a unique context where small-scale irrigation is expanding, but overextraction and competition over groundwater have not yet reached alarming levels. The groundwater game, adapted from Meinzen-Dick et al. (2016 and 2018), was played in 15 villages, accompanied by community-wide debriefing discussions in each village after the game to reflect on the process and lessons learned, and to stimulate discussions around groundwater governance. We carried out participant surveys to capture individual mental models regarding groundwater use and management, as well as any immediate learning effects. Focus group discussions were held in each village prior to the intervention to establish a baseline and again six months after the intervention to assess possible lasting effects. The findings indicate cognitive, normative and relational learning, including increased understanding of groundwater dynamics (such as the joint effect of diverse water uses and users), the importance of collective action in resource management, and the benefits of communication. We find gendered differences in decision-making about resource extraction in the game and evolvement of group-level resource management across no-communication, communication, and rule-making rounds of the game. We discuss community-wide learning and institutions-building, and considerations for future intervention designs. We recommend embedding experiential learning, facilitated by local extension officers or other community engagement practitioners, in intervention packages that include both technical assistance on water-conserving technologies and management approaches and support in building communities’ institutional capacity.